Impact of a Large-Scale Mold Intervention in Public Housing on Asthma Emergency Department Visits - Nina M Flores; Joan A Casey; Stephanie Lovinsky-Desir; Ariel Spira-Cohen; Sybille Louis; Sarah Walters; Maureen Little; Jungang Zou; Kara E Rudolph; Diana Hernández; Qixuan Chen; Matthew S Perzanowski (American Journal of Respiratory and Critical Care Medicine, 2026)
Abstract Rationale Over 300,000 predominantly Black, Hispanic, and low-income NYC residents live in New York City Housing Authority (NYCHA) buildings. For decades, NYCHA residents have experienced both frequent mold complaints and substantial asthma burden. In 2019, NYCHA implemented ‘Mold Busters,’ an evidence-based, authority-wide program to reduce mold in their buildings. Objectives To test the hypothesis that the ‘Mold Busters’ intervention reduced asthma-related emergency department (ED) visits for NYCHA residents. Methods We obtained 2016-2023, building-level asthma-related ED visit data among NYCHA residents and a ‘Mold Busters’ unexposed group living in proximate, non-NYCHA lower-income census tracts. We assessed the impact of ‘Mold Busters’ using doubly robust differences-in-differences analyses. We incorporated mold report, extreme precipitation, building, and neighborhood data to assess intervention efficacy. Measurements and Main Results ‘Mold Busters’ was associated with an average annual reduction of 7.2 (95% CI: -9.6, -4.8) asthma-related ED visits per 1,000 residents, translating to 2,200 fewer annual visits from 2022-2023 (19% lower than expected). Mold reports decreased post-‘Mold Busters,’ but still increased following extreme precipitation events. Among buildings with the largest decreases in mold reports post-intervention, reductions in visit rates were as large as 12.0 (-16.9, -7.0) per 1,000 residents. Results were stronger among adults than children and in spring and winter months than in other months. Conclusions To our knowledge, this is the first large-scale observational study to demonstrate that a city-wide mold intervention in public housing substantially reduced asthma ED visits. Housing interventions on asthma triggers could play a critical role in reducing longstanding asthma disparities. Subject Categories 2.11, 1.15, 6.01, 6.20, 1.17